Acute appendicitis characterization in pediatrics patients. Cienfuegos, 2013-2018 - Luis Enrique Jiménez Franco; Carlos Alberto Cabrera Machado (Medisur)
Foundation: the acute appendicitis’ behavior study offers a general view of its etiology and severe forms; guarantees the action protocols adequacy in order to improve specialized medical care. Objective: to characterize the acute appendicitis behavior in pediatric patients. Methods: a descriptive study was carried out at the Paquito González Cueto University Pediatric Hospital, in Cienfuegos, from 2013 to 2018. For the total cases corresponding to the studied period (N=933), the analyzed variables were: age, sex, year of diagnosis, municipality of origin, type of acute appendicitis and complications presence. Descriptive statistics and epidemiological indicators were applied. Results: Patients between the ages of 10 and 14 years (57.87%) predominated, as well as males (54.34%), for an incidence rate of 17.65 cases per 10,000 inhabitants. The Cienfuegos municipality was the most representative, with 377 patients (40.41%). The cases with acute catarrhal appendicitis (75.34%) and uncomplicated forms (91.63%) stood out. Conclusions: acute appendicitis behaved variably depending on the temporal relationship; in correspondence with the ages and sex of highest incidence. It manifested itself mainly in its milder stages, related to uncomplicated forms.